"It's Luck as to What Sort of Family You're Born Into" Cumulative Dis/advantage Generative Systemic Processes Across the Life Course of a Baby-Boom Birth Cohort. (1st February 2020) - Wildman, Josephine M
Abstract: Objectives: While a large body of evidence exists in support of outcomes associated with cumulative dis/advantage (CAD), individual-level experiences of the systemic processes that generate unequal outcomes have received far less attention. This study explored experiences, among members of an early baby-boom birth cohort, of CAD-generative processes within the education and housing systems and the mechanisms by which they interacted with initial social position to perpetuate inequalities. Methods: The author conducted in-depth interviews ( n = 27) with members of the Newcastle Thousand Families Study, a UK 1947 birth cohort. Longitudinal survey data enabled participant sampling on the basis of gender, occupational social class at birth and age 50, educational attainment and homeownership status at age 60. Qualitative data were analyzed using thematic analysis. Results: Analysis identified two themes: Firstly, the sorting and funneling mechanisms by which the "meritocratic" education system interacted with initial social position, progressively narrowing aspirations and opportunities; and secondly, the creation in later life of winners and losers in the property market, resulting in legitimization of inequalities through a deservingness narrative. Discussion: CAD has proved persistent, even among the supposedly "lucky" early baby-boom cohort. Policies to ameliorate CAD generation through education and property systems act instead to entrench advantaged social positions. Later-life outcomes can be naturalized as the product of effort-plus-ability if not seen in a whole-life context. Disruption of CAD processes requires challenging vested interest inherent in social systems.